The use of vegetable and animal protein-based supplements in strength training (Research, Society and Development, 2021)
Introduction: Nutritional protein supplementation is an important need when it comes to strength training, and it is important to know about the use of these supplements in consideration of their origin, whether animal or vegetable. Objective: This study aimed to analyze, through bibliographic findings, the importance of using animal and vegetable proteins in strength training. Methodology: With the bibliographical survey, it was possible to identify that the market currently has a very diversified range of protein supplements, both of animal and vegetable origin, the first being the most prominent in quantity and variety. Results and Discussion: When comparing the results found with regard to strength training and individuals who use protein supplements of animal and vegetable origin, the studies analyzed did not show a significant difference between both supplements, which indicates that the two types of supplements Proteins are effective as expected in strength training. Conclusion: there is no significant difference in strength training results considering both supplements, requiring further research in this field.